Feasibility Analysis of Organic Rice (Oryza Sativa L) Farming in Sambirejo Village, Banyuasin 1 District - Oktariani, Lisna; Yanti, Melly (Talenta Publisher, 2022)
The community is currently running the Back to Nature movement. It is considered a response to today’s lifestyle activities that are considered unhealthy to cause various kinds of diseases. Organic rice farming in Sambirejo Village has been implemented since 2018, although not all farmers have cultivated organically in their farming. This research aims to determine the feasibility of organic rice farming and determine the impact of organic fertilizer on the organic rice production rate in Sambirejo Village, Banyuasin 1 District. The research was carried out from February 2021 to June 2021. Locations were selected intentionally. The research method was in the form of a direct survey of organic rice farmers. For respondents, 30 farmers were taken using a simple random method. This research indicates that the average income earned by organic rice farmers is Rp. 5,703,254/Ha/planting season, with a proportion of R/C 1.65. Organic rice is feasible to cultivate when viewed from the proportion of R/C value that provides additional revenue for each additional revenue. Variable use of organic fertilizer has a positive, real and significant effect on increasing organic rice production, based on the result of calculated t value of 9.245 which is greater than t table. So that organic rice farming is very feasible for development in Sambirejo Village.